Legal Analysis of the Appointment of Guardians for the Protection of Minors Based on a Will in Indonesian Civil Law: A Study of Court Decision No. 184/Pdt.G/2022/PN Medan - Sulastri Febriana Purba; Janpatar Simamora; Ria Juliana Siregar (Al-Risalah, 2026)
Minors are legally considered incapable of performing legal acts and therefore require legal protection through guardianship. In civil law, guardianship functions as a substitute for parental authority over children who are not under the care of their parents, including the management of the child’s personal and property interests. One form recognized in Indonesian civil law is testamentary guardianship, namely the appointment of a guardian through a will. However, in practice, the implementation of testamentary guardianship does not always align with the best interest principle of the child, particularly when the guardian’s authority may potentially affect the protection of the child’s rights and assets. This study aims to analyze the legal validity of testamentary guardianship and examine the judge’s legal considerations in determining guardianship in Medan District Court Decision Number 184/Pdt.G/2022/PN.Mdn. The research employs normative legal research using statutory, conceptual, and case approach methods. Primary legal materials include provisions of the Indonesian Civil Code concerning guardianship, while secondary materials consist of legal doctrines and relevant scholarly literature. The findings indicate that the appointment of a guardian through a will is not absolute and must be assessed against the best interest principle. Judges evaluate several factors, including the legal validity of the will, the moral integrity and responsibility of the proposed guardian, and the emotional relationship between the guardian and the child. This article contributes to the development of civil law discourse by highlighting the limitations of testamentary guardianship in practice and emphasizing that guardianship should function primarily as a mechanism of child protection, rather than merely as a legal instrument for controlling or managing the child’s assets.